2017
DOI: 10.3389/fmicb.2017.00409
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Abundances Predict Methane and Nitrous Oxide Fluxes from a Windrow Composting System

Abstract: Manure composting is a significant source of atmospheric methane (CH4) and nitrous oxide (N2O) that are two potent greenhouse gases. The CH4 and N2O fluxes are mediated by methanogens and methanotrophs, nitrifying and denitrifying bacteria in composting manure, respectively, while these specific bacterial functional groups may interplay in CH4 and N2O emissions during manure composting. To test the hypothesis that bacterial functional gene abundances regulate greenhouse gas fluxes in windrow composting systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 86 publications
(131 reference statements)
3
12
0
Order By: Relevance
“…Levels of AOB gene copies were lower than those seen in studies of agricultural waste compost, where they ranged from log 8–10 g −1 at the start of composting (though decreased to undetectable levels by the end of composting) (Zeng et al, 2011). Another study, of manure composts, found lower AOB gene copy numbers (log 2.5–4.5 g −1 DM) that increased over time (Li et al, 2017), as seen in this study.…”
Section: Resultssupporting
confidence: 85%
“…Levels of AOB gene copies were lower than those seen in studies of agricultural waste compost, where they ranged from log 8–10 g −1 at the start of composting (though decreased to undetectable levels by the end of composting) (Zeng et al, 2011). Another study, of manure composts, found lower AOB gene copy numbers (log 2.5–4.5 g −1 DM) that increased over time (Li et al, 2017), as seen in this study.…”
Section: Resultssupporting
confidence: 85%
“…The total methane emission increase was to the tune of 28. . This period generally corresponds with increased availability of root sloughing or exudates due to peak photosynthetic activity and advanced root senescence and might probably provide more substrate for methanogenesis (Allen et al, 2003;Tokida et al, 2010;Li et al, 2017). The results from the present experiment also demonstrated that nitrogen fertilization increased the methane flux irrespective of [CO 2 ].…”
Section: Total Methane Emissionsupporting
confidence: 64%
“…Structural genes appear to correlate well to the activity catalyzed by the respective encoded enzymes, as has been shown for methanogenesis and methane oxidation (41)(42)(43)(44), as well as other microbe-mediated processes, e.g., 2-methyl-4-chlorophenoxyacetic acid, an herbicide, degradation (45), and N-cycling processes (46). Determining the gene abundances before and after incubation, we relate the magnitude change in the mcrA and pmoA genes to the total methane produced and oxidized, respectively (Fig.…”
Section: Discussionmentioning
confidence: 56%